An acute bout of exercise modulates both intracortical and interhemispheric excitability. (24th April 2017) - Neva, J. L.; Brown, K. E.; Mang, C. S.; Francisco, B. A.; Boyd, L. A.
Abstract: Primary motor cortex (M1) excitability is modulated following a single session of cycling exercise. Specifically, short‐interval intracortical inhibition and intracortical facilitation are altered following a session of cycling, suggesting that exercise affects the excitability of varied cortical circuits. Yet we do not know whether a session of exercise also impacts the excitability of interhemispheric circuits between, and other intracortical circuits within, M1. Here we present two experiments designed to address this gap in knowledge. In experiment 1, single and paired pulse transcranial magnetic stimulation (TMS) were used to measure intracortical circuits including, short‐interval intracortical facilitation (SICF) tested at 1.1, 1.5, 2.7, 3.1 and 4.5 ms interstimulus intervals (ISIs), contralateral silent period (CSP) and interhemispheric interactions by measuring transcallosal inhibition (TCI) recorded from the abductor pollicus brevis muscles. All circuits were assessed bilaterally pre and two time points post (immediately, 30 min) moderate intensity lower limb cycling. SICF was enhanced in the left hemisphere after exercise at the 1.5 ms ISI. Also, CSP was shortened and TCI decreased bilaterally after exercise. In Experiment 2, corticospinal and spinal excitability were tested before and after exercise to investigate the locus of the effects found in Experiment 1. Exercise did not impact motor‐evoked potential recruitment curves, Hoffman reflex or V‐wave amplitudes. These results suggest that a session of exercise decreases intracortical and interhemispheric inhibition and increases facilitation in multiple circuits within M1, without concurrently altering spinal excitability. These findings have implications for developing exercise strategies designed to potentiate M1 plasticity and skill learning in healthy and clinical populations. Abstract : This study demonstrates that measures of bilateral intracortical circuitry and interhemispheric excitability are modulated after a session of cycling exercise. Specifically, intracortical inhibition decreased, facilitation increased and interhemispheric inhibition decreased after acute exercise. Interestingly, there were no changes in spinal excitability. These findings have potential implications for exercise to enhance excitability and skill learning in healthy and clinical populations.